Clothing Capers Leaders Guide - Joy Cantrell Jordan; R. Nadine Hackler; Johannah Pourciau (EDIS, 2002)
Produced by the Department of 4-H and Other Youth Programs and Department of Home Economics, University of Florida Cooperative Extension, Institute of Food and Agricultural Sciences, June, 1996; reviewed June 2002.